2018
DOI: 10.3389/fpls.2018.01395
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Expression Patterns of Auxin Response Factors in Wheat

Abstract: Auxin response factors (ARFs) are important transcription factors involved in both the auxin signaling pathway and the regulatory development of various plant organs. In this study, 23 TaARF members encoded by a total of 68 homeoalleles were isolated from 18 wheat chromosomes (excluding chromosome 4). The TaARFs, including their conserved domains, exon/intron structures, related microRNAs, and alternative splicing (AS) variants, were then characterized. Phylogenetic analysis revealed that members of the TaARF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 83 publications
0
23
0
Order By: Relevance
“…tumdia is a popular vegetable in China, and becoming geographical indication products of Chongqing city. In recent years, ARF genes have gained widespread attention due to the large number of family members and their response to most of life processes in plants, and ARFs were genome-wide identified in Arabidopsis, rice, maize and wheat successively [6,7,8,9]. In this study, we characterized 65 B.juncea ARF genes by genome-wide analysis (S1 Table), which is a higher number than reported in other species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…tumdia is a popular vegetable in China, and becoming geographical indication products of Chongqing city. In recent years, ARF genes have gained widespread attention due to the large number of family members and their response to most of life processes in plants, and ARFs were genome-wide identified in Arabidopsis, rice, maize and wheat successively [6,7,8,9]. In this study, we characterized 65 B.juncea ARF genes by genome-wide analysis (S1 Table), which is a higher number than reported in other species.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of BjARF gene expression showed that these genes could be divided into four groups, and partial BjARF members were significantly expressed in plant tissues or different varieties. Many ARFs (AtARF2, AtARF7, AtARF19, OsARF1, OsARF5, OsARF19, OsARF24, SlARF2, and SlARF19) were found to be involved in regulating the development of plant roots, stems, leaves and flowers [9,20,31,51,52]. In this study, 12 candidate genes were subjected to expression pattern analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokinin is a key regulator of plant cell division [41]. In this study, genes positively correlated with the biosynthesis of cytokines were significantly upregulated in triploid, while other genes playing a negative regulation role were downregulated in triploid.…”
Section: Endogenous Hormone-related Degsmentioning
confidence: 50%
“…It is a phenyl-urea compound that has been substantiated to have the cytokinin potency across plant species [24][25][26][27]. Growth regulators' signal conversions into metabolic activities and developmental morphologies in cells or organisms have been established in biology [28][29][30][31][32][33]. The concept is broadly utilized for downstream applications particularly in cell, tissue, and organ cultures as well as plant transformation across plant species [24,[34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%